2020
DOI: 10.1007/s00702-020-02274-z
|View full text |Cite
|
Sign up to set email alerts
|

Emotional well-being and pain could be a greater determinant of quality of life compared to motor severity in cervical dystonia

Abstract: Non-motor symptoms (NMS) occur in patients with cervical dystonia (CD) but with variable frequencies and impact on health-related quality of life (HRQoL). To define non-motor and motor profiles and their respective impact on HRQoL in CD patients using the newly validated Dystonia Non-Motor Symptoms Questionnaire (DNMSQuest). In an observational prospective multicentre case–control study, we enrolled 61 patients with CD and 61 age- and sex-matched healthy controls (HC) comparing demographic data, motor and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 55 publications
3
29
0
1
Order By: Relevance
“…In the current study, pain/discomfort was reported by 68.2% of the patients with CD. Inconsistent with our results, pain has also been identified to affect the quality of life in patients with CD in several studies (7)(8)(9)(11)(12)(13). The pain in CD can be relieved by botulinum toxin injection (28).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, pain/discomfort was reported by 68.2% of the patients with CD. Inconsistent with our results, pain has also been identified to affect the quality of life in patients with CD in several studies (7)(8)(9)(11)(12)(13). The pain in CD can be relieved by botulinum toxin injection (28).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, multivariate linear regression analysis showed that EQ-5D-5L health utility scores were associated with disease duration, motor severity, and nonmotor symptoms, including pain, depression, and sleep quality, while EQ VAS scores were only associated with non-motor symptoms, including pain and depression. As with our results, non-motor symptoms have been widely reported to play an important role in the decreased quality of life in isolated dystonia, including CD (12,24,25). Approximately 55∼90% of the patients with CD have been reported to suffer from pain (1,26,27).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a recent publication by Klingelhöfer et al, pain, insomnia and stigma were most prevalent, and emotional well-being and pain had a major impact on quality of life. Most NMS, with the exception of pain, stigma and daily activity, did not correlate with motor severity [29].…”
Section: Non-motor Symptoms and Rating Scalesmentioning
confidence: 89%
“…In addition to abnormal head postures, many patients present with so-called non-motor symptoms (NMS) [28][29][30]. It is a matter of debate whether these are direct or indirect symptoms of the disease.…”
Section: Non-motor Symptoms and Rating Scalesmentioning
confidence: 99%